Widening access to writing support: beliefs about the writing process are key. Issue 8 (14th September 2019) - Kempenaar, Larissa; Murray, Rowena
Abstract: Universities' performance indicators for scholarly outputs depend on academics having productive and sustainable writing behaviours. Research shows that writing programmes can increase research output, but less is known about which writing processes are productive. A project was initiated at a university which widened access to writing support to include staff who were not included in these performance targets, but who might be in the future. Following a writing for publication workshop, 36 academics were offered a place at a structured writing retreat. The evaluation aimed to increase our understanding of participants' perceptions of their writing skills and processes before and after the retreat using a transactional model. We found that participants' perceptions of their writing abilities were greater than their perceptions of their ability to employ effective writing practices. Both scores improved after the retreat. This finding confirms that a structured writing retreat provides an environment and structure for academics to practise effective writing. It enhances self-belief in the processes and skills required to produce output. Widening access to writing support for academics is essential for success in performance-based systems. Writing support must provide opportunities for academics to develop strong performance beliefs by practising writing skills and productive and sustainable writing processes.